Timing of sedimentation, metamorphism, and plutonism in: The Helgeland Nappe Complex, north-central Norwegian Caledonides - Barnes, Calvin G. (TTU); Frost, Carol D.; Yoshinobu, Aaron S. (TTU); McArthur, Kelsey; Barnes, Melanie A. (TTU); Allen, Charlotte M.; Nordgulen, Øystein; Prestvik, Tore (Geosphere, 2007)
None The Helgeland Nappe Complex consists of a sequence of imbricated east-dipping nappes that record a history of Neoproterozoic- Ordovician, sedimentary, metamorphic, and magmatic events. A combination of U-Pb dating of zircon and titanite by laser-ablation- inductively coupled plasma-mass spectrometry plus chemostratigraphic data on marbles places tight constraints on the sedimentary, tectonic, and thermal events of the complex. Strontium and carbon isotope data have identifi ed Neoproterozoic marbles in the Lower Nappe, the Horta nappe, and Scandian-aged infolds in the Vikna region. The environment of deposition of these rocks was a continental shelf, presumably of Laurentia. Detrital zircon ages from the Lower Nappe are nearly identical to those of Dalradian sedimentary rocks in Scotland. Cambrian rifting caused development of one or more ophiolitefl oored basins, into which thick sequences of Early Ordovician clastic and carbonate sediments were deposited. On the basis of ages of the youngest zircons, deposition ended after ca. 481 Ma. These basin units are now seen as the Skei Group, Sauren-Torghatten Nappe, and Middle Nappe, as well as the stratigraphically highest part of the Horta nappe and possibly of the Upper Nappe. The provenance of these sediments was partly from the Lower Nappe, on the basis of detrital zircon age populations in metasandstones and cobbles from proximal conglomerates. However, the source of Cambrian-Ordovician zircons in all of the Early Ordovician basins is enigmatic. Crustal anatexis of the Lower and Upper Nappes occurred ca. 480 Ma, followed by imbrication of the entire nappe sequence. By ca. 478 Ma, the Horta nappe was overturned and was at the structural base of the nappe sequence, where it underwent migmatization and was the source of S-type magmas. Diverse magmatic activity followed ca. 465 Ma, 450-445 Ma, and 439-424 Ma. Several plutons in the youngest age range contain inherited 460-450 Ma zircons. These zircons are interpreted to refl ect a deep crustal zone in which ...